A study of staff pre-evacuation behaviors in a Malaysian hotel - Noumeur, Abdelmoutaleb; Lovreglio, Ruggiero; Md Said, Mohamad Syazarudin; Mohd Tohir, Mohd Zahirasri; Baharudin, Mohd Rafee; Mohamed Yusoff, Hamdan (John Wiley and Sons, 2024)
Simulating fire and evacuation scenarios is crucial for engineers to assess buildingsafety during fire incidents. Accurate simulations require data on occupants' behav-iors, particularly during the pre-evacuation phase as these decisions significantlyimpact evacuation duration. Gathering comprehensive data from diverse regionswhile considering cultural and regional variations is necessary to understand howoccupants' behavior is influenced. Thus, this study focuses on examining the behaviorof Malaysian hotel staff during unannounced fire drill to gain insights into factorsaffecting their behavior during pre-evacuation stage, such as fire experience, firealarm, drill participation, fire training, and awareness. The study categorizes theactions performed by the hotel staff into sequences and analyses them based oninfluencing factors. The findings indicate that instead of immediately evacuating inresponse to emergency notification, the hotel staff engage in various actions. Moststaff members initially investigate or ignore the emergency, resulting in longer pre-evacuation times. Moreover, the results suggest that previous drill participation andhigh awareness levels contribute to shorter pre-evacuation times. Conversely, previ-ous fire experience, fire training, and fire alarm familiarity have no effect on pre-evacuation time.